1976
DOI: 10.1159/000465585
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Equilibrium Constant and Heterogeneity Index on Anti-Rh(0)(D) Quantitation Using the Auto-Analyser

Abstract: Thermodynamic and kinetic considerations, based on a standard bromelin/ methylcellulose method for anti-Rh(0)(D) quantitation using the Auto-Analyser, have shown that the proportion of antibody bound at equilibrium and its rate of attainment is dependent on the mean equilibrium constant and heterogeneity index of the particular antibody preparation. Also, upon dispersal of the deliberately induced rouleaux, a new state of equilibrium is defined, the rate of attainment of which is related to the equilibrium con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
1981
1981

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Since it has been shown that estimates of anti-D concentration made by AutoAnalyzer methods are appreciably affected by variations in equilibrium constants (Gunson et al, 1976), it should be pointed out that the figures given in Table I1 assume that equilibrium constants did not vary widely in the samples tested. Moreover, it should be mentioned that although the British Working Standard, which is defined in international units, was used, results have been expressed as pg anti-D assuming that the relationship between i.u.…”
Section: Discussionmentioning
confidence: 99%
“…Since it has been shown that estimates of anti-D concentration made by AutoAnalyzer methods are appreciably affected by variations in equilibrium constants (Gunson et al, 1976), it should be pointed out that the figures given in Table I1 assume that equilibrium constants did not vary widely in the samples tested. Moreover, it should be mentioned that although the British Working Standard, which is defined in international units, was used, results have been expressed as pg anti-D assuming that the relationship between i.u.…”
Section: Discussionmentioning
confidence: 99%